The potential of Dark Septate Endophytes to form root symbioses with ectomycorrhizal and ericoid mycorrhizal middle European forest plants - Lukešová, Tereza; Kohout, Petr; Větrovský, Tomáš; Vohník, Martin (PloS one, 2015)
The unresolved ecophysiological significance of Dark Septate Endophytes (DSE) may be in part due to existence of morphologically indistinguishable cryptic species in the most common Phialocephala fortinii s. l.--Acephala applanata species complex (PAC). We inoculated three middle European forest plants (European blueberry, Norway spruce and silver birch) with 16 strains of eight PAC cryptic species and other DSE and ectomycorrhizal/ericoid mycorrhizal fungi and focused on intraradical structures possibly representing interfaces for plant-fungus nutrient transfer and on host growth response. The PAC species Acephala applanata simultaneously formed structures resembling ericoid mycorrhiza (ErM) and DSE microsclerotia in blueberry. A. macrosclerotiorum, a close relative to PAC, formed ectomycorrhizae with spruce but not with birch, and structures resembling ErM in blueberry. Phialocephala glacialis, another close relative to PAC, formed structures resembling ErM in blueberry. In blueberry, six PAC strains significantly decreased dry shoot biomass compared to ErM control. In birch, one A. macrosclerotiorum strain increased root biomass and the other shoot biomass in comparison with non-inoculated control. The dual mycorrhizal ability of A. macrosclerotiorum suggested that it may form mycorrhizal links between Ericaceae and Pinaceae. However, we were unable to detect this species in Ericaceae roots growing in a forest with presence of A. macrosclerotiorum ectomycorrhizae. Nevertheless, the diversity of Ericaceae mycobionts was high (380 OTUs) with individual sites often dominated by hitherto unreported helotialean and chaetothyrialean/verrucarialean species; in contrast, typical ErM fungi were either absent or low in abundance. Some DSE apparently have a potential to form mycorrhizae with typical middle European forest plants. However, except A. applanata, the tested representatives of all hitherto described PAC cryptic species formed typical DSE colonization without specific structures necessary for mycorrhizal nutrient transport. A. macrosclerotiorum forms ectomycorrhiza with conifers but not with broadleaves and probably does not form common mycorrhizal networks between conifers with Ericaceae.
Keywords: Picea; mykorhiza; Mycorrhizae; smrk; Endophytes; endofyty; symbióza; Europe; Evropa; Plant Roots; Symbiosis; kořeny rostlin